Jorge Amado in the USSR: allowed printed, “dangerous” on the big screen - Darmaros, Marina Fonseca (Brasiliana: Journal for Brazilian Studies, 2018)
The present article aims at sketching a panorama of the screening and reception of film adaptations of Jorge Amado’s works produced between the 1970s and 1980s and exhibited in the Soviet Union on different platforms and to analyze these choices.